Phytochemical insights into flavonoids in cancer: Mechanisms, therapeutic potential, and the case of quercetin - Silva-Pinto, Piero Alex; de Pontes, Janaína Teixeira Costa [UNESP]; Aguilar-Morón, Brigitte; Canales, Christian Shleider Carnero; Pavan, Fernando Rogério [UNESP]; Roque-Borda, Cesar Augusto (Elsevier, 2025)
Quercetin, a flavonoid known for its potent antioxidant and anti-inflammatory properties, has gained attention in cancer therapy due to its ability to modulate key molecular pathways involved in tumor progression and immune evasion. This review provides a comprehensive analysis of quercetin's effects on pathways such as PI3K/Akt/mTOR, MAPK/ERK, NF-κB, and JAK/STAT, which are central to cancer cell survival, proliferation, and apoptosis. Through inhibition of PI3K/Akt/mTOR and MAPK/ERK signaling, quercetin promotes apoptosis and reduces proliferation specifically in cancer cells while sparing healthy cells. Additionally, quercetin downregulates NF-κB activity and modulates JAK/STAT signaling, enhancing immune recognition of cancer cells and decreasing inflammation in the tumor microenvironment. Emerging nanoformulation strategies are also discussed, highlighting how nanotechnology can improve quercetin's bioavailability and targeting capabilities. Unlike other reviews, this work uniquely integrates molecular insights with cutting-edge nanoformulations, showcasing quercetin's dual potential as a therapeutic agent and an immune modulator in the evolving landscape of cancer treatment. This review underscores quercetin's multifaceted role in cancer treatment and suggests future directions to optimize its clinical efficacy, particularly in combination with conventional therapies.
Keywords: Antioxidants; Flavonoids; JAK/STAT; Nanoformulations; NF-κB; PI3K/Akt/mTOR; Quercetin; Signaling pathways; Tumor microenvironment